COMPUTER TECHNOLOGY AND COMPETITIVE ADVANTAGE OF SELECTED MEDIA HOUSES IN KENYA - Ngutu, Emma; Wanjira, Dr. Jane (European Journal of Business and Strategic Management, 2016)
Purpose: The main objective of the study was to establish the influence of computer technology on the competitive advantage of selected media houses in Kenya. Methodology: The study adopted a descriptive research design. Findings: Results revealed that adoption of computer technology influenced the competitive advantage of selected media houses in Kenya. Therefore, the study concluded that computer technology influenced the competitive advantage of selected media houses in Kenya. The conclusion was informed by the realization that computerized software adoption, online mobile application and use of internet influenced the competitive advantage of selected media houses in Kenya. The study also concluded that staff training had a moderating effect on the relationship between technology and competitive advantage of selected media houses in Kenya. Unique contribution to theory, practice and policy: The study would be of value to the media industry in Kenya. This is due to the fact that the media industry has experienced increased competition from new media such as the internet and social media making the competition stiffer and survival harder. The study would therefore provide relevant information to these media houses on how computer technology affects their competitive advantage. Hence, this information can give the media houses insight on which strategies to adopt so as to ensure competitiveness. Consumers of media would benefit from this study as the study creates awareness that use of new media is cheaper. This would also assist to increase the adoption of technology in Kenya. The findings of this study would also be significant to academicians in that it will add to the body of knowledge of the researchers in this field of study.